2022
DOI: 10.3390/nu14183765
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolism of Naringin and the Impact on Antioxidant Capacity

Abstract: Naringin is a dietary flavonoid glycoside with broad bioactivities, and it has been found to undergo extensive microbial metabolism in human gut. Microbial metabolites are believed to play an important role in the overall bioactivity of naringin. However, knowledge is scarce about its microbial metabolism in laboratory rats, which are the most commonly used animal model for naringin-related biomedical studies. Herein, we profiled the microbial metabolism of naringin in rat by an in vitro anaerobic fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…More interestingly, the experimental results showed that the prototypes with similar structures could be converted into others by hydrogenation or dehydrogenation, methylation or demethylation, and hydroxylation or dehydroxylation in phase I metabolism [38–41]. The absorbed constituents and the proposed metabolic pathways of the constituents in Radix Cudramiae extract after oral administration are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…More interestingly, the experimental results showed that the prototypes with similar structures could be converted into others by hydrogenation or dehydrogenation, methylation or demethylation, and hydroxylation or dehydroxylation in phase I metabolism [38–41]. The absorbed constituents and the proposed metabolic pathways of the constituents in Radix Cudramiae extract after oral administration are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary antioxidants supplementation in hens could improve egg production via enhancing hepatic antioxidant capacity, thereby alleviating lipid metabolism disorders ( Miao et al, 2021 ; Zhang et al, 2022 ). Naringin has been proven to be an excellent plant-derived antioxidant ( Gercek et al, 2021 ; Hassan et al, 2021 ; Zeng et al, 2022 ). Goliomytis et al (2015) reported that the addition of naringin to the diet could increase antioxidant capacity in broiler meat.…”
Section: Discussionmentioning
confidence: 99%
“…It exists as light yellow crystalline powder at room temperature. Naringin exhibits high antioxidant capacity attributed to its many functional groups, including hydroxy and carbonyl groups ( Chen et al, 2016 ; Zeng et al, 2019 ; Zeng et al, 2022 ). Previous studies demonstrated that dietary naringin supplementation improved the antioxidant capacity of broiler and lamb meat ( Goliomytis et al, 2015 ; Simitzis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the important role of these microbial metabolites in the overall bioactivity of NRG [ 19 , 20 ]. In fact, the physiological effects of NRG cannot be fully achieved in the absence of microbial metabolites due to the extensive biotransformation of the parent compound [ 21 ]. Although significant conversion takes place in the colon, some breakdown also occurs in the distal portion of the small intestine [ 22 ].…”
Section: Bioavailability and Pharmacokinetic Properties Of Naringinmentioning
confidence: 99%